Damage Detection in Gusset Plates of Steel Truss Bridges using Modal Parameters: Experimental and Numerical Study - Kristijanto, Heppy; Fitriyah, Dita Kamarul; Habieb, Ahmad Basshofi (Civil Engineering Dimension, 2025)
Corrosion in gusset plate elements has become a critical factor in bridge structural failures, emphasizing the need for more accurate and reliable damage detection methods. Conventional visual inspections are limited in precision and cannot provide real-time monitoring, underscoring the importance of advanced techniques. This study proposes a vibration-based Structural Health Monitoring (SHM) approach employing modal parameter indices, namely Mode Shape (MS), Mode Shape Curvature (MSC), Mode Shape Slope (MSS), and Mode Shape Curvature Square (MSCS), to detect damage in bridge components. Damage scenarios were simulated by introducing gusset plate cuts of 5%, 10%, and 20% to represent different levels of corrosion. The results indicate that MSC and MSCS are the most reliable methods for identifying damage locations in complex structural systems, as they capture mode shape alterations with high sensitivity. Furthermore, the accuracy of modal parameter analysis improves with increasing damage severity. These findings confirm MSC and MSCS as robust tools for early-stage corrosion detection in SHM applications.